Lymphatic dissemination of HPV-positive oropharyngeal squamous cell carcinoma: underlying mechanisms and treatment innovations - Li, Xinyu; Qiu, Hui; Wu, Qiuji (Frontiers in Immunology, 2025)
Cancers, with its rising incidence strongly linked to human papillomavirus (HPV) infection, particularly HPV16. HPV-induced OPSCC (HPV-OPSCC) exhibits distinct biological behaviors, including a high propensity for early lymphatic metastasis, occurring in most of cases, often presenting as cystic lymph node changes. The rising incidence of HPV-positive OPSCC is associated with specific mechanisms, particularly the characteristic biological behaviors driven by the E6/E7 oncoproteins: E7 disrupts cell cycle control by degrading pRb protein, while E6 inhibits apoptotic pathways through ubiquitination-mediated degradation of p53. Despite advances in treatment, HPV-OPSCC poses unique challenges due to its complex tumor microenvironment and immune interactions. Tertiary lymphoid structures (TLS) within the tumor microenvironment play a critical role in modulating anti-tumor immunity, correlating with improved clinical outcomes. Recent advances in immunotherapy, such as immune checkpoint inhibitors and HPV-specific vaccines, have shown promise in enhancing patient survival. This review explores the mechanisms of HPV-driven carcinogenesis, the clinical and molecular features of lymphatic metastasis, and the emerging role of TLS and immunotherapeutic strategies in HPV-OPSCC. By analyzing existing evidence, this review seeks to clarify the distinct biological features of HPV-associated oropharyngeal squamous cell carcinoma (HPV-OPSCC) and guide the development of novel treatment strategies aimed at enhancing clinical outcomes for patients. (OPSCC)